Students’ Mathematical Literacy Ability in Learning Using Rally Coach-Schoology Model with Diagnostic Assessment - Pertiwi, Rizki Dian; Kartono, Kartono; Wardono, Wardono (Universitas Negeri Semarang, 2019)
Students’ low mathematical literacy ability causes the need for a learning using the right model. media and assessment to fix it. One of the alternatives is Rally Coach-Schoology model with diagnostic assessment. This research aims (1) to know the quality of learning using Rally Coach-Schoology model with diagnostic assessment towards the students’ achievement of mathematical literacy ability. and (2) to describe the results and follow-ups of diagnostic assessment in such learning. This quantitative research was done by quasi experimental design. The population was the students grade VIII of SMPN 4 Semarang in 2017/2018 academic year with the students of VIII D and VIII E as samples. The data were collected by documentation. observations. giving tests and questionnaire. and validations by experts. Data analysis was done both empirically and statistically using one-sample t test. proportion test. independent-samples t test and proportions comparison test. Results showed that (1) the learning using Rally Coach-Schoology with diagnostic assessment was qualified towards the achievement of students’ mathematical literacy ability. and (2) both students with low and moderate mathematical literacy ability had difficulties in relating problems to the useful concepts for problem solving. while students with high mathematical literacy ability were careless in doing mathematical operations. The follow-ups were done by peer tutoring and giving certain assignments according to students’ difficulties. therefore students’ mathematical literacy ability could be developed which can be seen from the average score of their final test results 74.58 and 88% of them got scores above the minimal completeness criteria.